Corticosteroids and Azathioprine Do Not Prevent Radiation-Induced Lung Injury - Eva Kwok; Charles K Chan (Canadian Respiratory Journal)
The case of a man who presented with dyspnea and a dry cough six weeks after mediastinal radiotherapy for malignant thymoma is described. The patient was on prednisone (30 mg/day) and azathioprine (100 mg/day) throughout the course of radiation. The respiratory difficulties developed as the dose of prednisone was gradually decreased to 20 mg/day postradiation. Chest x-ray showed bilateral pulmonary infiltrates. Computed tomography scan of the thorax confirmed bilateral ground glass opacities, with well-defined lateral margin on the right side corresponding to the field of radiation. However, the airspace opacities extended beyond the radiation field into the periphery of the lungs together with mild airway dilation on the left side compatible with bronchiolitis obliterans organizing pneumonia (BOOP) or cryptogenic organizing pneumonia. Bronchoalveolar lavage performed on the nonirradiated area showed an intense lymphocytosis. No cause of BOOP other than radiation was found. Treatment with high dose corticosteroids (80 mg/day) resulted in rapid clinical and radiological improvement, and resolution of chest x-ray abnormalities. Focal mediastinal radiation therapy may induce diffuse lung injury including BOOP. In addition, the concurrent use of moderate dose prednisone and azathioprine during the periradiotherapy period does not prevent the development of either BOOP or classic radiation pneumonitis.